The Quantitative Analyses for the Effects of Two Wheat Varieties With Different Resistance Levels on the Fungicide Control Efficacies to Powdery Mildew - Wang, Aolin; Zhao, Yanan; Zhang, Meihui; Yuan, Junhai; Liu, Wei; Fan, Jieru; Hu, Xiaoping; Zhou, Yilin (Frontiers in Plant Science, 2022)
The effective strategies to reduce the occurrence of wheat powdery mildew are the use of resistant varieties and application of fungicides. However, most of studies rarely focused on the quantitative value of fungicide reduction using resistant varieties. To explore how the fungicides performed on different resistant wheat varieties to powdery mildew, field experiments were conducted during wheat growing seasons in 2018/19 and 2019/20 to investigate the control efficacies of enostroburin·epoxiconazole 18% SC and triadimefon 20% EC to wheat powdery mildew on highly resistant wheat variety (‘Baofeng104’) and highly susceptible wheat variety (‘Jingshuang16’). The analyses of variance on control efficacies showed that the control efficacies of enostroburin·epoxiconazole 18% SC to wheat powdery mildew were mostly significantly higher than triadimefon 20% EC under the same conditions (i.e., varieties, dosages). However, both fungicide and variety resistance made variabilities in the mildew disease index and played a significant role in mildew management. Particularly, the variety resistance made the greatest contribution in mildew-reducing, and the disease index could significantly be reduced on highly resistant variety even in the absence of fungicide treatment. The control efficacies to mildew on highly susceptible variety mainly depended on the high efficiency of fungicides whereas on highly resistant variety which were mainly by virtue of variety resistance through the comparative analyses of linear regression models. Furthermore, the random-coefficient regression models and quantile models quantificationally expounded that the relationships between active ingredient dosage and disease index or control efficacy varied from the effects of variety, fungicide, and year, particular from variety. Thus, a dosage reference table of enostroburin·epoxiconazole 18% SC or triadimefon 20% EC for different resistant wheat varieties were provided, it would be helpful for users to formulate an appropriate dosage of fungicide on mildew management in the field and avoid overusing or superfluous application. Further study needs to be considered the effects of fungicide reduction on wheat yields, only then the maximum-economic benefits on mildew management can be determined.